Solving simple equations with brackets

Equation with brackets Example 1 

5x+3(x-6)=7x+13        After expanding the brackets the equation becomes

5x + 3x -18 = 7x +13  the numbers containing x need to be moved on one side of the = sign and the resto of the numbers moved on the other side.

8x-7x= 13+18

x=31

Equation with brackets Example 2 

4(x+5)-3(x-3)=2(x+5)

4x+20+3x+9=2x+30     After expanding the brackets, the equation becomes

4x-3x-2x=30-29   the numbers containing x need to be moved on one side of the = sign and the resto of the numbers moved on the other side of the = sign

-x=1 multiply by (-) to change the signs

x=-1

Equation with brackets Example 3

5(x+2)+4(x+2)=3(x+8)+12

5x+10+4x+8=3x+24+12 After expanding the brackets the equation becomes

9x+18=3x+36 the numbers containing x need to be moved on one side of the = sign and the resto of the numbers moved on the other side of the = sign

9x-3x=36+18

6x=18

x=3

 

Primary tutor

QTS numeracy tutors

Biology tutor

11+ Maths tuition

QTS numeracy practice

 

Print Friendly